Soft competencies and employability of vocational school graduates – the perspective of employers from the Świętokrzyskie Voivodeship - Wiśniewska, Sylwia; Wiśniewski, Kamil (Kompetencje miękkie a zatrudnialność absolwentów szkół zawodowych – perspektywa świętokrzyskich pracodawców, 2019)
The aim of the article is to determine the importance of soft competencies in developing the employability of vocational school graduates in the opinion of employers from the Świętokrzyskie Voivodeship. The article presents literature studies and analyzes the results of empirical research using the IBM Predictive Solution 5. The study shows the essence of soft competencies and employability as well as the specificity of vocational education in the context of contemporary labour market requirements. The next part of the article presents the methodological assumptions of the research and the research sample statistics. The last part of the article discusses the results of surveys carried out among enterprises from the Świętokrzyskie Voivodeship. The final part of the article indicates the limitations of the completed tests and the directions of further research in the discussed area
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 9, s. 211-223
Keywords: soft competency; employability; vocational education; Świętokrzyskie Voivodeship; kompetencje miękkie; zatrudnialność; szkolnictwo zawodowe; województwo świętokrzyskie